PENINGKATKAN PEMAHAMAN DAN KETERAMPILAN MELALUI OPTIMALISASI SUMBER DAN ALAT DALAM MENULIS KARANGAN EKSPOSISI PESERTA DIDIK DI MAN BONDOWOSO: MAN BONDOWOSO - HARTATIK HARTATIK (Dewan Pendidikan Bondowoso, 2021)
Writing activities are often a frightening problem for students, the obstacles experienced by students when students compile an essay, often students lack vocabulary in expressing their ideas through writing. Writing skills are an activity that is inseparable from students' teaching and learning activities in school. Writing activities make students active in learning activities and stimulate students' skills in arranging words. However, in practice, many people find it difficult to get students used to learning to write. In order to improve students' understanding of the subject matter, the authors implement learning improvements through classroom action research. This research was conducted by the teacher alone because it has several benefits, including: helping teachers improve learning, helping teachers develop professionally, increasing self-confidence, and enabling teachers to actively develop knowledge of writing skills. Besides the benefits felt by the teacher, this research is also beneficial for students, namely: helping students channel their ideas / ideas, improving students' abilities about writing skills, increasing student activity in writing essays, and so on